Nurses and Physicians Attitudes toward Nurse-Physician Collaboration: A Survey from Gaza Strip, Palestine - Aymen Elsous; Mahmoud Radwan; Samah Mohsen (Hindawi Limited, 2017)
Interprofessional collaboration and teamwork between nurses and physicians is essential for improving patient outcomes and quality of health services. This study examined the attitudes of nurses and physicians toward nurse-physician collaboration. A cross-sectional study was conducted among nurses and physicians (n=414) in two main referral public hospitals in the Gaza Strip using the Arabic Jefferson Scale of Attitude toward Physician-Nurse Collaboration. Descriptive statistics and difference of means, proportions, and correlations were examined using Student's t-test, one-way ANOVA, and Pearson correlation and p<0.05 was considered as statistical significant. Response rate was 42.8% (75.6% for nurses and 24.4% for physicians). Nurses expressed more positives attitudes toward collaboration than physicians (M ± SD on four-point scale: 3.40±0.30 and 3.01±0.35, resp.) and experience duration was not proved to have an interesting influence. Teamwork approach in the professional practice should be recognized taking into consideration that the relationship between physicians and nurses is complementary and nurses are partners in patient care.